A study on optical sensors orientation for tomography system development - Abdul Shaib, M. Fadzli; Abdul Rahim, Ruzairi; M. Muji, Siti Zarina; Leow, Pei Ling; Abdul Jamil, M. Mahadi (International Frequency Sensor Association (IFSA), 2012)
This paper describes the investigation of optical sensors performance towards the development of optical tomography system. The orientation of the transmitters has been set from 0o until 180o and then the receiver’s responses were analyzed. Hence, sensors capabilities were tested further by placing blockage object in between the transmitter and receiver and the effect of this arrangement were observed. Finally, new designs of sensor jig were introduced based on the results achieved. Copyright © 2012 IFSA.